Skin cancer-related conditions managed in general practice in Australia, 2000–2016: a nationally representative, cross-sectional survey - Sanchia Aranda; Gillian Reyes-Marcelino; Joanne F Aitken; Anne E Cust; Caroline G Watts; Christopher Harrison; Yoon-Jung Kang; Pascale Guitera; Kirstie McLoughlin (BMJ Open, 2023)
Objective Skin cancer is Australia’s most common and costly cancer. We examined the frequency of Australian general practice consultations for skin cancer-related conditions, by patient and general practitioner (GP) characteristics and by time period.Design Nationally representative, cross-sectional survey of general practice clinical activity.Setting, participants Patients aged 15 years or older having a skin cancer-related condition managed by GPs in the Bettering the Evaluation And Care of Health study between April 2000 and March 2016.Primary outcome measures Proportions and rates per 1000 encounters.Results In this period, 15 678 GPs recorded 1 370 826 patient encounters, of which skin cancer-related conditions were managed 65 411 times (rate of 47.72 per 1000 encounters, 95% CI 46.41 to 49.02). Across the whole period, ‘skin conditions’ managed were solar keratosis (29.87%), keratinocyte cancer (24.85%), other skin lesion (12.93%), nevi (10.98%), skin check (10.37%), benign skin neoplasm (8.76%) and melanoma (2.42%). Over time, management rates increased for keratinocyte cancers, skin checks, skin lesions, benign skin neoplasms and melanoma; but remained stable for solar keratoses and nevi. Skin cancer-related encounter rates were higher for patients aged 65–89 years, male, living in Queensland or in regional or remote areas, with lower area-based socioeconomic status, of English-speaking background, Veteran card holders and non-healthcare card holders; and for GPs who were aged 35–44 years or male.Conclusion These findings show the spectrum and burden of skin cancer-related conditions managed in general practice in Australia, which can guide GP education, policy and interventions to optimise skin cancer prevention and management.